2015
DOI: 10.1080/10426914.2015.1004685
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Tool Wear During the Electrochemical Discharge Machining

Abstract: Electrochemical discharge machining is a nonconventional machining method which can be used to machine nonconductive materials such as glass and ceramics. However, machining of the refractory materials such as ceramics requires high voltages to produce the required thermal energy. In this condition, the tool wear would be increased significantly. This paper reports the study of the wear of the different tool materials. The selected tool materials have different melting/boiling temperatures responding to the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…The auxiliary electrode (anode) was a stainless steel 304L block of size 100×50×10 mm and the cathode was a tapered-tip WC tool with diameter of 500 µm. The reason for using WC as the tool material was its high resistance against the tool wear in the glass machining voltages [8]. Also Soda-lime glass slides of size 75×25×1 mm were used as the workpiece and two DC power supplies (0-60 V, 0-5 A) were employed to apply the required working and offset voltages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The auxiliary electrode (anode) was a stainless steel 304L block of size 100×50×10 mm and the cathode was a tapered-tip WC tool with diameter of 500 µm. The reason for using WC as the tool material was its high resistance against the tool wear in the glass machining voltages [8]. Also Soda-lime glass slides of size 75×25×1 mm were used as the workpiece and two DC power supplies (0-60 V, 0-5 A) were employed to apply the required working and offset voltages.…”
Section: Methodsmentioning
confidence: 99%
“…ECDM process can be employed to machine hard, brittle and nonconductive materials in a reasonable time and cost with acceptable aspect ratio and low damages to the workpiece [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Hajian et al [14] investigated effects of magnetic field orientation on ECDM performance and concluded that magnetic field orientation increased channel depth and surface quality. Behroozfar and Razfar studied characteristics on the plasma channel and material removal [15] and tool wear [16] during ECDM. Dhanvijay and Ahuja [17] studied machining parameters of stagnant and electrolyte flow method on ECDM and obtained the results that electrolyte flow method had a high MRR but a high diametric overcut that had been minimized.…”
Section: Ecdmmentioning
confidence: 99%
“…The vibration assistance to the electrolyte improved the spark stability by ensuring the availability of electrolyte at the machining zone throughout the process. Cheng et al [20] applied a magnetohydrodynamic convection (MHD) to enhance the electrolyte circulation, thereby preventing the deterioration of gas film quality with the increase in machining depth. The technique reduced the machining time and improved the entrance diameter of the holes produced.…”
Section: Introductionmentioning
confidence: 99%
“…The use of maintaining tool as anode increased the rate of cutting quartz, but produced significant tool wear. As an attempt to study the tool wear mechanisms in ECDM, Ali et al [20] conducted experiments using different tool materials under different conditions. They reported that the tool wear mechanism depends upon the tool material composition and the tungsten was identified as the most suitable material for high-voltage application.…”
Section: Introductionmentioning
confidence: 99%